Coping with an Evil World: Contextualizing the Stress-Buffering Role of Scripture Reading - DeAngelis, Reed T.; Acevedo, Gabriel A.; Vaidyanathan, Brandon 1980-; Ellison, Christopher G. 1960- (2021)
This research note advances the religious coping literature by testing whether belief in an evil world conditions the stress-moderating role of scripture reading. Hypotheses are tested with original data from a survey of black, Hispanic, and white American churchgoers from South Texas (2017–2018; n = 1,115). Our findings show that reading scripture for insights into the future attenuates the positive association between major life events and psychological distress, but only for congregants who do not believe the world is fundamentally evil and sinful. For congregants who believe the world is evil, scripture reading amplifies the association between life events and distress. Whether scriptural coping is beneficial for mental health could be contingent on a believer's broader assumptions about the nature of the world we live in.
Keywords: Mental Health; stress process; major life events; religious and spiritual struggles; Religious Coping; scriptural coping